The impact of “At-the-Border” and “Behind-the-Border” policies on cost-reducing research and development - Berthoumieu, Julien; Bouët, Antoine (International Food Policy Research Institute, 2015)
This research paper is aimed at understanding why border trade policies are today complemented with behind-the-border policies like output subsidies, R&D subsidies, and public R&D investments. This is a new type of protectionism that becomes prominent since the 2006-2008 economic crisis. In this paper we analyze the impact of various policies on domestic cost-reducing research and development (R&D) expenditures using an international duopolistic model with uncertainty regarding the result of the R&D process. We examine the impact of “at-the-border” policies (import tariffs, import quotas, voluntary export restraints, and minimum price agreements) as well as “behind-the-border” policies (output subsidies, R&D subsidies, and public R&D investments). We demonstrate new theoretical findings, in particular the increasing then decreasing impact of quotas on R&D, as well as the impact of production subsidies, public R&D investments, and minimum price agreements on private R&D. We conclude that R&D subsidies are appealing policy instruments because they support not only domestic R&D expenditures but also domestic production and profits without reducing consumers’ surplus.